Implementasi Protokol Geographic Source Routing(GSR) Pada Vehicular Ad-Hoc Network(VANET) untuk Komunikasi Kendaraan Dengan Road Side Unit(RSU) - Rezky Hadiwiriyanto; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Vanet (Vehicular Ad Hoc Network)is a type of wireless network that provides communication vehicles that serve as its nodes. Vanet has three elements, namely among vehicle to vehicle communication (V2V), vehicle to infrastructure (V2I) and infrastructure to infrastructure (I2I). This study focuses on the communication vehicle to infrastructure such as Road Side Unit (RSU). Various problems arise in the design of Vanet, one of them is the use of a protocol that is not in accordance with the criteria and mechanism of action of the Vanet. In this study, the protocols in use are the GSR and AODV protocol which are implemented and compared based on the scenarios research which are the density of the vehicle, the vehicle speed and the number of RSU's variations specify the protocol works best on Vanet environment. Implementation is performed using (NS-2) and SUMO. The results of the GSR and AODV protocol implementation are analyzed based on the test parameters are throughput, end-to-end delay and packet delivery ratio. From the test results, protocols AODV has a better performance in scenarios density and speed of the vehicle with the parameters throughput and packet delivery ratio with a value of 1004 bps and 99.65%, while the GSR better its performance on parameters of end-to-end delay with a value of 2.35 ms. In scenario number variation RSU, GSR protocol has better performance parameters of throughput and end-to-end delay with a value of 4060 bps and 2,531 ms while AODV protocol, better on the parameters of packet delivery ratio with a value of 99.83%.